How Mongolian herders perceive ecological change in a "stable" landscape - Batdelger Gantuya (Resilience Alliance, 2021)
Recently, climate change has had a considerable impact on rangelands, available forage, and shifting boundaries of ecological zones in Mongolia. Additionally, long-term studies in the forest-steppe zone show that increasing livestock pressure impacts vegetation composition and cover. Evidence shows that the traditional ecological knowledge of Mongolian herders can serve as a valuable body of information relevant to observations about these ongoing ecological processes. Among other things, a deeper understanding of how herders perceive ecological changes would be useful for improving pasture management and promoting natural regeneration processes. We conducted indoor and outdoor structured and semi-structured interviews, with additional landscape walks and participatory fieldwork. In total we interviewed 33 people, all full-time herders. We found 32 indicators on how herders perceived landscape and vegetation changes for the 14 habitat types studied. Herders had deep knowledge of their landscape, and they attributed various changes to diverse drivers on their grasslands, wetlands, and forests. Among herders there was variation in the perceived importance of droughts and increasing livestock numbers. The perceived changes and indicators could be grouped into three main categories, namely long-term (decadal) trends, regenerative successions after disturbance, and recurrent fluctuations caused mainly by weather. Some of the long-term trends reported by herders are well-known, e.g., worsening of rangeland production, others, like the blackening of tussocks, or the impact of oilskin on yurt site regeneration, are rarely mentioned in the scientific literature, if at all. South-facing mountain slopes and flat areas in valleys were reported as the locations where vegetation change takes place most rapidly. To reverse adverse changes, herders wish to cooperate especially with each other to increase mobility, stop overgrazing, and help nature to regenerate their worsening pastures. We conclude that herders have a reliable and widely shared understanding of landscape and pasture changes that could help with this cooperation.